Last gate of the emperor - Mbalia, Kwame; Makonnen, Joel, Prince, 1982- (Scholastic Press, 2021)
Gamer Yared Heywat lives a lonely existence in the city of Addis Prime with his uncle Moti and his bionic lioness Besa. When his favorite online game forces him to play using his real identity, high-tech monsters swarm the city looking for him and kidnap his uncle. Yared teams up with fellow video gamer Ibis to avoid capture, and learns that the stories about the lost space empire of Axum are true and he is at the heart of the stories.